Pacific cupped oyster - Crassostrea gigas - Lapegue, Sylvie; Boudry, Pierre; Goulletquer, Philippe (Actes Workshop Genetics of domestication, breeding and enhancement of performance of fish and shellfish, Viterbo, Italy, 12-17 june 2006, pp.74-80, 2006)
Originating from the north eastern Asia, Crassostrea gigas is endemic to Japan, but has been introduced and translocated, mainly for aquaculture purpose, into several countries, almost worldwide (1). In North America, the species can be found from Southeast Alaska to Baja California, while in European waters the species is cultured from Norway to Portugal as well as in Mediterranean Sea (Fig.1) (2). Biological characteristics make it suitable for a wide range of environmental conditions, although it is usually found in coastal and estuarine areas within its natural range. Although highly variable, the invasiveness pattern of C. gigas has been demonstrated in several countries and therefore considered as a pest or a noxious species in those areas (3).